MY SAY: Accountable politicians needed - Abd Razak, Dzulkifli (2010)
WANTED — for failing our democracy." This is a fullpage advertisement placed in the respected daily, The Guardian (UK, March 22), referring to a group of named Members of Parliament who allegedly committed the "stated crime". "The days of the rotten Parliament are almost over. The fight for a reforming Parliament begins now," the ad claims. The ad is a clear demonstration of how critical of the performance of some of their elected representatives some sections of British society have become. Though six were singled out and their "mug shots" published, the ad said there are many like them who "have stood in the way of cleaning up and reforming our politics". "No matter what their party, if they're an MP who has blocked democratic reform or attacked civil liberties, they'll be held to account for their record," it said emphatically.